PEMBUATAN DATABASE UNTUK PENGELOLAAN PERPUSTAKAAN DESA - Argaditia Mawadati; Muhammad Albar Dharmasakti; Afan Tulus Satria (LPPM IST AKPRIND Yogyakarta, 2020)
Karang Taruna Citra Muda Desa Madurejo Yogyakarta has a long-term project which is currently being worked on and implemented, namely the Village Library and the Garbage Bank. For the village library project, the implementation is considering not optimal yet and the management finds it difficult to manage the village library because of the limited members who are willing to voluntarily manage the library. Thus in this community service activity, we teach them how to make a database for the village library so that it can help ease the task of the library management. The method used is counseling as well as practicing to make and operate the database. The results of this counseling carried out by devotees is a village library database which can be updated continuously in the future by the management team. The use of databases in library management can help ease the burden of library managers and can help improve the arrangement of books, which can then indirectly increase interest in visiting and reading interest of the community.